Estimating a high-frequency New Keynesian Phillips curve - Steffen Ahrens; Stephen Sacht (Kiel University, Department of Economics, 2011)
This paper estimates a high-frequency New Keynesian Phillips curve via the Generalized Method of Moments. Allowing for higher-than-usual frequencies strongly mitigates the well-known problems of small-sample bias and structural breaks. Applying a daily frequency allows us to obtain estimates for the Calvo parameter of nominal rigidity over a very short period - for instance for the recent financial and economic crisis - which can then be easily transformed into their monthly and quarterly equivalences and be employed for the analysis of monetary and fiscal policy. With Argentine data from the end of 2007 to the beginning of 2011, we estimate the daily Calvo parameter and find that on average, prices remain fixed for approximately two to three months which is in line with recent microeconomic evidence.
Keywords: C26; E31; 330; Calvo Staggering; High-Frequency NKM; GMM